Identification of the semaphorin receptor PLXNA2 as a candidate for susceptibility to schizophrenia - Mah, S; Nelson, M R; DeLisi, L E; Reneland, R H; Markward, N; James, M R; Nyholt, D R; Hayward, N; Handoko, H; Mowry, B; Kammerer, S; Braun, A (Molecular psychiatry, 2006)
The discovery of genetic factors that contribute to schizophrenia susceptibility is a key challenge in understanding the etiology of this disease. Here, we report the identification of a novel schizophrenia candidate gene on chromosome 1q32, plexin A2 ( PLXNA2 ), in a genome-wide association study using 320 patients with schizophrenia of European descent and 325 matched controls. Over 25 000 single-nucleotide polymorphisms (SNPs) located within approximately 14 000 genes were tested. Out of 62 markers found to be associated with disease status, the most consistent finding was observed for a candidate locus on chromosome 1q32. The marker SNP rs752016 showed suggestive association with schizophrenia (odds ratio (OR)=1.49, P =0.006). This result was confirmed in an independent case–control sample of European Americans (combined OR=1.38, P =0.035) and similar genetic effects were observed in smaller subsets of Latin Americans (OR=1.26) and Asian Americans (OR=1.37). Supporting evidence was also obtained from two family-based collections, one of which reached statistical significance (OR=2.2, P =0.02). High-density SNP mapping showed that the region of association spans approximately 60 kb of the PLXNA2 gene. Eight out of 14 SNPs genotyped showed statistically significant differences between cases and controls. These results are in accordance with previous genetic findings that identified chromosome 1q32 as a candidate region for schizophrenia. PLXNA2 is a member of the transmembrane semaphorin receptor family that is involved in axonal guidance during development and may modulate neuronal plasticity and regeneration. The PLXNA2 ligand semaphorin 3A has been shown to be upregulated in the cerebellum of individuals with schizophrenia. These observations, together with the genetic results, make PLXNA2 a likely candidate for the 1q32 schizophrenia susceptibility locus.